Perspectives on pregnant women's educational needs to prevent TB complications during pregnancy and the neonatal period. A qualitative study - LB Khoza; SA Mulondo; RT Lebese (BMC, 2023)
Abstract Background Tuberculosis (TB) during pregnancy could confer a high risk for maternal and infant morbidity. Literature indicates that the global burden of active TB disease among pregnant women is not well researched. Statistics for South Africa from WHO give an estimated incidence of 360, 000 cases of TB in 2019; 14,000 people became ill with multidrug-resistant TB in 2019, with a rate of 615 per 100,000 population, implying that the cohorts included pregnant women with and without a diagnosis of TB infection. Therefore, the study aims to increase the understanding of the educational needs required to prevent TB complications during pregnancy and the neonatal period in women diagnosed with TB infection. Methods The study used cross-sectional qualitative and descriptive designs to collect data in the clinical setting of the primary health care services of Limpopo Province, South Africa. The population comprised pregnant women diagnosed with TB infection. A non-probability purposive sampling technique was used to sample 2 health centers and 5 clinics in each of the three sampled districts. The targeted sample size was 63 and it was achieved even though data saturation was observed. Individual interviews were conducted, audiotaped, and transcribed. Guided by the study questions, a thematic content analysis of the findings was used. Ethical considerations were also observed. Results Despite that pregnant women have general knowledge about TB disease, the knowledge and awareness regarding the prevention of TB complications in pregnancy and the neonatal period, information on TB/HIV and COVID-19 co-infections, and participants' knowledge about other non-infectious diseases that may affect the mother with TB infection and foetus showed a deficit. Conclusion Pregnant women with TB disease need to be educated on the negative effects of non-adherence to TB treatment during pregnancy and the neonatal period. There is a need to educate pregnant women about the variant signs and symptoms of TB, HIV and COVID-19 infections since there is a misconception that the three diseases are similar. It is important that pregnant mothers diagnosed with TB should start treatment as soon as possible.